Mengkaji Penyebab Tingkah Laku Abnormal Tokoh Sasana Dalam Novel Pasung Jiwa Karya Okky Madasari Menggunakan Teori Coleman (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The aim of this research is to describe the causes of the abnormal behavior experienced by the gym characters in the novel Pasung Jiwa by Okky Madasari. This research uses Coleman's theory about four causes of abnormal behavior. This research method uses a qualitative descriptive method. Data collection uses reading techniques and note-taking techniques, as well as including theories from several books and data found, then described and analyzed. The results obtained in this research, the character in the novel Pasung Jiwa, namely Sasana, has causes that make him have abnormal behavior, including primary causes, predisposing causes, triggering causes and strengthening causes.